Application of Interactive Powerpoint Media In Improving Learning Outcomes In Numerical Number Material For Grade Iv Students - Erlangga, Perlian; Martanilova, Helen; Elta, Fitria; Nazira, Nazira; Marwa, Marwa; Firdaus, Firdaus (Jurnal Pendidikan Tambusai, 2024)
Learning media is an important component in the learning process, but in reality there are still very few teachers who use media in the learning process, causing student learning outcomes to decline. This research aims to reveal 1) whether the application of interactive PowerPoint media can improve mathematics learning outcomes in whole number material, 2) how the application of interactive PowerPoint media can improve mathematics learning outcomes in whole number material. This research method is Classroom Action Research using quantitative and qualitative approaches. Data collection techniques in this research are tests, observation, interviews, documentation. The population of this study were all students in class IV-C of SDN 06 Belutu whose address was Jalan Perkebunan Ujung Tanjung, Jambai Makmur Village, Kandis District, Siak Regency with a total of 21 students. The research implementation and implementation procedures were divided into two cycles, each cycle held in two meetings. The results of this research show that student learning outcomes in cycle I obtained an average of 71.43 with a completion percentage of 76.19% and the number of students who achieved the KKM was 16 students, after improvements were made in cycle II it showed that student learning outcomes had increased to 86 .19 with a completion percentage of 90.47% with 19 students achieving the KKM. By using interactive PowerPoint learning media on whole number material, it has characteristics that can make it easier for teachers to convey the material, make it easier for students to understand the material, students feel happier, their ability to work in groups looks better with indications: students are more active, work becomes more effective, students obey orders, and communication is clearer. Digital-based PowerPoint media adapts to technological developments and can be used for a long period of time. This interactive PowerPoint learning media is designed with an attractive and interactive design. Apart from the material, it also includes games and quiz questions which can encourage student activity in participating in learning and are able to create interaction between the learning media and students so that it can improve student learning outcomes in a whole number of materials. class IV SDN 06 Belutu academic year 2023/2024.